2016
DOI: 10.1039/c6ra17291a
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable and blue-emitting copper nanocluster dispersion prepared by magnetron sputtering over liquid polymer matrix

Abstract: For the first time, magnetron sputtering of copper onto liquid was investigated for the preparation of stable blue-fluorescent copper nanoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 33 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…S9c †). 24,43,44 These results suggest that more electrons were lost for Cu in G-R-CuNCs-1 compared to G-CuNCs-1. Furthermore, it could be observed that Cu 2p for R-CuNCs-0 showed even more positive peaks for both Cu 2p 3/2 and Cu 2p 1/2 at 932.7 eV and 952.6 eV, respectively (Fig.…”
Section: Comparison Of the Properties Of The Cuncsmentioning
confidence: 82%
“…S9c †). 24,43,44 These results suggest that more electrons were lost for Cu in G-R-CuNCs-1 compared to G-CuNCs-1. Furthermore, it could be observed that Cu 2p for R-CuNCs-0 showed even more positive peaks for both Cu 2p 3/2 and Cu 2p 1/2 at 932.7 eV and 952.6 eV, respectively (Fig.…”
Section: Comparison Of the Properties Of The Cuncsmentioning
confidence: 82%
“…Molten salt [64], vegetable oil [65,66], biomolecules [67], fatty acids [68], multifunctional group ligandcontaining liquids [69,70], polyol [71] and others have been examined as candidates for liquid sputtering to offer different surface functionality for the particles and to understand the influence of the liquid medium on particle growth. Recently, there has been great progress in particle size control on a scale from sub-nano to a few nanometres via the addition of thiol functionalized protecting agents to the liquid matrix [72][73][74][75][76][77]. Consequently, fluorescent metal NCs and NCs hybridized in polymer resins were obtained.…”
Section: Brief History and Background Of Sputtering Onto A Liquidmentioning
confidence: 99%
“…4,15,25,26 The studies in this field reveal important roles of the liquid matrix in the growth behavior, size control, and colloidal stability of the sputtered nanoparticles. [1][2][3][4][5][6][13][14][15][16][17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Evaluating the impact of the physicochemical properties of the liquids on the particle size helped understand the particle formation. 6,18,19,[27][28][29][30][31][32][33][34][35][36][37][38] For example, when Au was sputtered onto ionic liquids, the particle nucleation could o...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][13][14][15][16][17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Evaluating the impact of the physicochemical properties of the liquids on the particle size helped understand the particle formation. 6,18,19,[27][28][29][30][31][32][33][34][35][36][37][38] For example, when Au was sputtered onto ionic liquids, the particle nucleation could occur on the liquid surface and growth could occur on the liquid surface and/or in the bulk liquid. [27][28][29][30]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation